2016
DOI: 10.1038/srep36916
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Effects of Testosterone on the Sexually Dimorphic Transcriptome and Epigenome of Embryonic Neural Stem/Progenitor Cells

Abstract: The mechanisms by which sex differences in the mammalian brain arise are poorly understood, but are influenced by a combination of underlying genetic differences and gonadal hormone exposure. Using a mouse embryonic neural stem cell (eNSC) model to understand early events contributing to sexually dimorphic brain development, we identified novel interactions between chromosomal sex and hormonal exposure that are instrumental to early brain sex differences. RNA-sequencing identified 103 transcripts that were dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 39 publications
3
39
0
Order By: Relevance
“…In line with the findings by Blankenhorn et al, reperfusion of infarcted rat hearts with female MSCs resulted in significantly increased recovery of left ventricular developed pressure compared to infarcted hearts treated with male MSCs [13]. Bramble et al [29,30] reported these transcriptional sex differences to be involved in cellular replication, indicating a differential regulation of proliferative and stemness states between male and female NSCs during development. Thus, intrinsic mechanisms defined by the sex seem a biologically relevant aspect of the protective and regenerative power of adult stem populations [13,14].…”
supporting
confidence: 68%
See 3 more Smart Citations
“…In line with the findings by Blankenhorn et al, reperfusion of infarcted rat hearts with female MSCs resulted in significantly increased recovery of left ventricular developed pressure compared to infarcted hearts treated with male MSCs [13]. Bramble et al [29,30] reported these transcriptional sex differences to be involved in cellular replication, indicating a differential regulation of proliferative and stemness states between male and female NSCs during development. Thus, intrinsic mechanisms defined by the sex seem a biologically relevant aspect of the protective and regenerative power of adult stem populations [13,14].…”
supporting
confidence: 68%
“…Bramble et al [29,30] revealed 103 differentially expressed transcripts between male and female murine embryonic neural stem cells using global gene expression analysis. Bramble et al [29,30] revealed 103 differentially expressed transcripts between male and female murine embryonic neural stem cells using global gene expression analysis.…”
Section: The Role Of Sex In Neuronal Development and Neural Stem Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…When compared before the onset of gonadal steroid production, more than 100 transcripts were differentially expressed between female (XX) and male (XY) stem cells. Intriguingly, stem cells of both sexes were responsive to testosterone treatment but not in the same way: thousands more transcripts varied in response to testosterone in XX stem cells than in XY stem cells 17 .…”
Section: Mechanisms Of Sexual Differentiationmentioning
confidence: 97%